(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Follicular development in the mammalian ovary is a complex process which is potentially regulated by an orchestrated action of the pituitary gonadotropins, e.g., follicle stimulating hormone (FSH) and luteinizing hormone (LH), and local ovarian factors, such as peptide growth factors and steroids. Along with hormonal activation it is necessary to have tight coordination of expression of genes during follicular development. This review highlights the structure and function of ovary, follicle and follicular development. This review also confirms the temporal and spatial expression of the specific genes and miRNAs and their involvement in different modulators, the synthesis of active factors, their interactions, and the dynamics of their receptors on the follicular cell surface may be the ultimate determinants of cellular events which are crucial to coordinated growth and differentiation of follicular cells leading to folliculogenesis and ovulation. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22355 Res. Agric., Livest. Fish.1(1): 47-60, Dec 2014